Arctic crustose coralline alga resilient to recent environmental change. Issue Volume 66:Issue S1(2021) Supplement (17th November 2020) - Williams, Branwen; Chan, Phoebe T. W.; Halfar, Jochen; Hargan, Kathryn; Adey, Walter
Abstract: Rising atmospheric carbon dioxide is warming Arctic seawater at a rate twice the global average due to multiple positive feedbacks. Thus, warming is disproportionately influencing data‐poor Arctic marine ecosystems. Subarctic flora are an important component of these ecosystems, along with the less biodiverse flora endemic to the Arctic. Warming will likely lead to an increasing dominance of subarctic flora that will be initially successful due to a shorter sea ice period. Benthic crustose coralline algae presently flourishes in subarctic regions where they are key substrate builders that influence community structure through provision of habitat for a variety of benthic organisms. Here we evaluate changes in the skeletal resilience of long‐lived subarctic crustose coralline alga Clathromorphum compactum to variability in seawater temperature and sea ice (the later which influences salinity and solar irradiance reaching the seafloor) across latitudes in the northwest Atlantic and Arctic Oceans. We demonstrate that average growth and calcification rate significantly decreases in C. compactum toward higher latitudes due to colder temperatures and more fresh waters. Skeletal density also declines toward higher latitudes but displays specimen‐specific variability. However, through a common growth period (1984–2001), density increased at all locations which we interpret to be a response to warmer and more well‐lit benthic environments. At the most northerly site, growth and calcification also increased with density, suggesting warming and declining Arctic sea ice in the spring may benefit this species at its upper latitudinal limits. As a result, continued warming may enhance the presence of C. compactum in Arctic regions.